Genomic analysis of six new Geobacillus strains reveals highly conserved carbohydrate degradation architectures and strategies - Brumm, Phillip J.; De Maayer, Pieter; Mead, David A.; Cowan, Don A. (Frontiers in Microbiology, 2015)
In this work we report the whole genome sequences of six new Geobacillus xylanolytic strains along with the genomic analysis of their capability to degrade carbohydrates. The six sequenced Geobacillus strains described here have a range of GC contents from 43.9% to 52.5% and clade with named Geobacillus species throughout the entire genus. We have identified a ~200 kb unique super-cluster in all six strains, containing five to eight distinct carbohydrate degradation clusters in a single genomic region, a feature not seen in other genera. The Geobacillus strains rely on a small number of secreted enzymes located within distinct clusters for carbohydrate utilization, in contrast to most biomass-degrading organisms which contain numerous secreted enzymes located randomly throughout the genomes. All six strains are able to utilize fructose, arabinose, xylose, mannitol, gluconate, xylan, and α-1,6-glucosides. The gene clusters for utilization of these seven substrates have identical organization and the individual proteins have a high percent identity to their homologs. The strains show significant differences in their ability to utilize inositol, sucrose, lactose, α-mannosides, α-1,4-glucosides and arabinan.